PESANTREN DAN MADRASAH SEBAGAI JEJAK PANJANG TRANSFORMASI LEMBAGA PENDIDIKAN ISLAM NUSANTARA - Ramadani, Suci; Nurzena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study traces the transformation of pesantren and madrasah as Islamic education institutions in the Nusantara region over time. The research employs a qualitative literature study with a historical approach, analyzing documents, journals, and academic articles related to the development of Islamic education. The analysis focuses on curriculum dynamics, educational systems, and the interaction between pesantren and madrasah, including their impact on Muslim generations in Indonesia. The results indicate that pesantren emphasize moral and spiritual development, while madrasah integrate religious education with general knowledge, making both institutions complementary and adaptive to social changes and educational policies. These findings highlight the critical role of pesantren and madrasah in shaping religious, competent, and character-driven Muslim generations. The study recommends further research on curriculum innovation and the use of educational technology to enhance the relevance of both institutions in the modern era.